2009
DOI: 10.1007/s11869-009-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study of short-range atmospheric dispersion for hypothetical air-borne effluent releases using different turbulent diffusion methods

Abstract: Radiological impact due to hypothetical air-borne effluent releases for an upcoming fast reactor (PFBR), at a tropical coastal site in Kalpakkam is studied using the HYSPLIT dispersion model. Short range air dispersion simulations are conducted with HYSPLIT for a weakly forced synoptic condition on 3rd March, 2008 with three turbulent diffusion methods, i.e., standard velocity deformation (A), short range isotropic similarity (B) and turbulent kinetic energy (TKE) (C) schemes to assess their performance in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…To more accurately model chloride dispersion from the ocean in domains in excess of 200 km, it is recommended that a particle model such as HYSPLIT be adopted into DUSTRAN. Though it is more computationally expensive, HYSPLIT has the ability to model in larger domains and can more effectively track vertical motion (Draxler and Hess 1997;Srinivas et al 2009). The DUSTRAN parameters were left at the default value; these may have a greater influence on dispersion and deposition than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…To more accurately model chloride dispersion from the ocean in domains in excess of 200 km, it is recommended that a particle model such as HYSPLIT be adopted into DUSTRAN. Though it is more computationally expensive, HYSPLIT has the ability to model in larger domains and can more effectively track vertical motion (Draxler and Hess 1997;Srinivas et al 2009). The DUSTRAN parameters were left at the default value; these may have a greater influence on dispersion and deposition than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…These dynamical phenomena signi cantly in uence the occurrence of several atmospheric processes such as e uent dispersion, evapotranspiration, and cloud formation (Srinivas et al, 2009;Katul et al, 2012;Babatunde et.al 2017;Poznicova, 2018;Bosman et al, 2018). Surface uxes are fundamental quantities for predicting boundary layer growth, atmospheric transport processes, and convective mixing (Liu et al, 2016;Park et al, 2017;Kim and Kwon, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that AC plays a significant role in the PM 10 dispersion and transport, being significantly related to vertical temperature variation (thermal gradient) and wind speed [15,16]. The latter variable also depends on the LC characteristics [17,18].…”
Section: Introductionmentioning
confidence: 99%